2014
DOI: 10.1111/cid.12238
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and Histological Evaluation of the Effects of Cortical Perforations on Bone Healing in Mandibular Onlay Graft Procedures

Abstract: In augmentation with mandibular onlay bone grafts, cortical perforations in the recipient site make no distinct contribution to bone healing within 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…It was found in several studies in animal models that cortical perforation did neither improve osteoblastic nor osteoclastic activity after healing, with no appreciable histological differences between the groups. Elsewhere, no differences in terms of augmented tissue, bone density, and thickness were reported, and even a better maintenance of the block thickness placed in the recipient area without perforations was observed 27,31,33,35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found in several studies in animal models that cortical perforation did neither improve osteoblastic nor osteoclastic activity after healing, with no appreciable histological differences between the groups. Elsewhere, no differences in terms of augmented tissue, bone density, and thickness were reported, and even a better maintenance of the block thickness placed in the recipient area without perforations was observed 27,31,33,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, no differences in terms of augmented tissue, bone density, and thickness were reported, and even a better maintenance of the block thickness placed in the recipient area without perforations was observed. 27,31,33,35,36 Nevertheless, other studies that support the effectiveness of perforating the cortex of the recipient site have been carried out, which described that it resulted in a more effective graft revascularization and bone formation during the initial stages of healing. [37][38][39][40] Other authors have also suggested the usefulness of performing perforations not only in the recipient bed but also in cortical grafts.…”
Section: Importance Of Perforating the Cortex Of The Recipient Sitementioning
confidence: 99%
“…Although perforations or decorticalization in the bone cortical of the receptor bone bed are widely performed with the aim of promoting revascularization and improving the incorporation process, 4–6,46,47 excessive resorption can occur in the receptor bone bed in which the graft can submerge, decreasing its volume and final thickness 6,46,47 . Conversely, when demineralization of the graft‐bed contacting surfaces was compared to perforations in rabbit tibial bone, no significant resorption was observed in the receptor bed and the graft volume was better preserved 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical techniques have been adopted to manage an extremely atrophic maxillary alveolar ridges such as guided bone regeneration (GBR), 1 cortical onlay bone grafting, 2 distraction osteogenesis, 3 and inlay technique 4 . Although these techniques are popular for augmentation of deficient alveolar bone, they were associated with a lot of complications such as additional surgical interventions with subsequent increase of the treatment cost and period, and donor site morbidity 5 …”
Section: Introductionmentioning
confidence: 99%